Past, Present and Future of FinTech Research: A Bibliometric Analysis - Ishtiaq Ahmad Bajwa; Shafiq Ur Rehman; Abid Iqbal; Zaheer Anwer; Murtaza Ashiq; Muhammad Ajmal Khan (SAGE Open, 2022)
This study has conducted a meta-literature review examining the past, present and possible future trends of Fintech research using 360 selected articles published between 2006 and June 2020. Both quantitative and qualitative techniques were applied. In the quantitative approach, a bibliometric citation analysis using HistCite and VOSviewer software was conducted and the qualitative analysis covered the identification of four main research streams related to (i) Bitcoin and digital currency, (ii) crowdfunding, (iii) mobile payment, and (iv) blockchain. The study results highlight the most influential aspects of the FinTech literature, such as the leading countries, institutions, journals, authors, and articles. Suggestions for the potential future direction of FinTech literature have also been made.